Relaciones intrafamiliares y su influencia en las conductas agresivas en una adolescente de 12 años - Leon Medina, Nathaly Estefania (2020)
The present case study was carried out in order to establish whether there is influence of intrafamily relationships in aggressive behaviors in adolescents, thus providing psychological counseling for each of the emotional and behavioral alterations due to the changes that were detected since the beginning. to study in the Barreiro educational unit which were the aggressiveness of others and believe that they can control the world as a result of family problems due to lack of affection, affection and communication, since with the psychological counseling the DECE department can continue with the respective treatment after having reviewed their records and having dealt with the patient during all sessions. The aggressive behaviors that the patient presented were the result of intrafamily problems at home since the institution only treated the behavior but with the performance of pre-professional practices and wanting to have a good job, I inquire more about the matter, and the Detonating was the lack of affection and aggressiveness towards her person by the breast in view of that the patient demonstrated what she learned at home, until the time treated with the patient there was collaboration in all sessions, due to the problem identified a therapeutic scheme to provide help to the patient and achieve a better life in both their family and school environment.